Evaluasi Ekonomi Mikro: Dampak Proyek Terpadu Peternakan dan Pertanian Pangan di Indonesia Bagian Timur - Budiman Notoatmojo (Bina Nusantara University, 2002)
Impact evaluation of integrated livestock and food crop project micro analysis will concentrate in the increase of farmers income, the increase of farmers food nutrient, and woman participation. Macro analysis has also been used to study on decentralization. The project has given 41.800 cattles for 19.000 farmers, 20.000 goats for 9 000 farmers, construct infrastructures (village road system, livestoc holding ground, etc), facilitate agroinputs for 28,000 package, training and extensions, and more others with total cost about US 34,200,000. The area covers South Sulawesi, North Sulawesi, Gorontalo , Maluku, and North East Maluku. Total number of samples which have been taken for the survey were 162, which consist of 27 women, 63 farmers, 18 project staf, and 18 respondent from outside project. The result from the survey has shown that farmers have got benefits from project and their income has increased. 79% farmers has satisfied with the credit they have received already, however, the repayment has moved slowly. Eventhough they have raised only chicken, however, the farmers’ food nutrient has increased already.